2008
DOI: 10.1007/s10067-008-0853-9
|View full text |Cite
|
Sign up to set email alerts
|

Hip involvement in juvenile idiopathic arthritis

Abstract: We analyzed the clinical, biological, and radiological aspects of hip involvement in juvenile idiopathic arthritis (JIA) in a developing country. The recruited patients fulfilled the International League Against Rheumatism criteria for the diagnosis of the JIA. Clinical, biological, and radiological parameters relating to the JIA were collected. Hip involvement was assessed according to clinical and radiological data related to hip disease. One hundred twenty-one patients were included (68 girls and 53 boys). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 4 publications
2
23
1
1
Order By: Relevance
“…Inflammation of the spine and coxofemoral joints is an indicator of more serious forms of the disease. 19,36,37 In our study, spreading to the cervical spine and coxofemoral joints arthritis were only found in children with detectable IL-17A values in the active phase of JIA. Therefore, children with detectable IL-17A levels should be closely monitored, and such results imply that, on the basis of IL-17A values in the initial phase of JIA, it may be possible to select patients at a higher risk from a worse functional outcome.…”
Section: Discussioncontrasting
confidence: 46%
“…Inflammation of the spine and coxofemoral joints is an indicator of more serious forms of the disease. 19,36,37 In our study, spreading to the cervical spine and coxofemoral joints arthritis were only found in children with detectable IL-17A values in the active phase of JIA. Therefore, children with detectable IL-17A levels should be closely monitored, and such results imply that, on the basis of IL-17A values in the initial phase of JIA, it may be possible to select patients at a higher risk from a worse functional outcome.…”
Section: Discussioncontrasting
confidence: 46%
“…Rostom et al 55 observed CR hip disease to start after 4 years of disease, whereas 80% had developed hip disease at 6 years, and 100% after 14 years. Other studies describing radiological features of JIA found most CR changes in the hands (57%), knees (47%), ankles (27%) and feet (36%), with erosions mainly in hands (18%) and feet (25%) 56.…”
Section: Resultsmentioning
confidence: 99%
“…4 Hip involvement in juvenile AS patients has been reported to be as high as 50%. 13 In juvenile-onset cases, bilateral involvement in which one side is more affected is frequently encountered. 13 In our study group, there was also bilateral synovial fluid and bone marrow edema in a patient who was 18 years old and who had been affected by the disease for four years.…”
Section: Discussionmentioning
confidence: 99%
“…13 In juvenile-onset cases, bilateral involvement in which one side is more affected is frequently encountered. 13 In our study group, there was also bilateral synovial fluid and bone marrow edema in a patient who was 18 years old and who had been affected by the disease for four years. In the patient group, the rate of early signs of hip involvement was found as 43.4%.…”
Section: Discussionmentioning
confidence: 99%